Vitamin D Actions on CD4+ T Cells in Autoimmune Disease - Hayes, Colleen Elizabeth; Hubler, Shane L.; Moore, Jerott R.; Barta, Lauren E.; Praska, Corinne E.; Nashold, Faye E. (Frontiers in Immunology, 2015)
This review summarizes and integrates research on vitamin D and CD4+ T-lymphocyte biology to develop new mechanistic insights into the molecular etiology of autoimmune disease. A deep understanding of molecular mechanisms relevant to gene–environment interactions is needed to deliver etiology-based autoimmune disease prevention and treatment strategies. Evidence linking sunlight, vitamin D, and the risk of multiple sclerosis and type 1 diabetes is summarized to develop the thesis that vitamin D is the environmental factor that most strongly influences autoimmune disease development. Evidence for CD4+ T-cell involvement in autoimmune disease pathogenesis and for paracrine calcitriol signaling to CD4+ T lymphocytes is summarized to support the thesis that calcitriol is sunlight’s main protective signal transducer in autoimmune disease risk. Animal modeling and human mechanistic data are summarized to support the view that vitamin D probably influences thymic negative selection, effector Th1 and Th17 pathogenesis and responsiveness to extrinsic cell death signals, FoxP3+CD4+ T-regulatory cell and CD4+ T-regulatory cell type 1 (Tr1) cell functions, and a Th1–Tr1 switch. The proposed Th1–Tr1 switch appears to bridge two stable, self-reinforcing immune states, pro- and anti-inflammatory, each with a characteristic gene regulatory network. The bi-stable switch would enable T cells to integrate signals from pathogens, hormones, cell–cell interactions, and soluble mediators and respond in a biologically appropriate manner. Finally, unanswered questions and potentially informative future research directions are highlighted to speed delivery of etiology-based strategies to reduce autoimmune disease.